The Income Level of Ecuador Families: Equity Factor for Consumption and Savings - Dueñas Solórzano, Ginger (2019)
The development of this article is focused on generating an analysis of the level of income of families in Ecuador: Equity factor for consumption and savings, a process that was generated based on the analysis of the gender equity of families of the sector and the impact on the levels of consumption and savings of the domestic economies, contrasting by means of the application of field information collection instruments, by means of which it was possible to determine that: The transitory dissaving of some families is influenced by low income and the presence of a single provider of income in the home, this situation raises the inequalities in the possibilities of savings in households in the urban versus rural sectors, with the conditions of labor market demand.